Essentials of business research methods - Hair, Joseph F.; Babin, Barry; Money, Arthur H.; Samouel, Phillip (Wiley & Sons, 2003)
This book covers the essentials of business research for managers. It includes coverage of the increasing role of knowledge management as well as how to conduct information-gathering activities more effectively in a rapidly changing business environment. Because managers increasingly must make decisions based on almost unlimited information in data warehouses, this text provides substantially more coverage of data analysis than other texts.